Penerapan Domain DSS Cobit 5 pada Analisis GAP dan Kecukupan Layanan Teknologi Informasi - Andini Sekarwati; Tiur Gantini; Saron Kurniawati Yefta (Jurnal Teknik Informatika dan Sistem Informasi, 2017)
Sustainability of         business processes remain awake will                        provide leverage to Maranatha DLTI in running the function of information technology in UKMs. To maximize service management information                                     system changes that                               are                                in the DLTI and Maranatha design and the transition of a new service or a change in management information systems at the service                     of DLTI in Maranatha. Control Objectives for Information and Related Technology (COBIT) 5. COBIT 5 is a comprehensive framework of large-scale enterprise and run it governance is already running. COBIT domain 5 domain chosen isDelivered, Service, and Support (DSS) that focus on the assessment of service delivery and information  technology as well as its support to business processes that take place including the management of the problem so that the sustainability of business processes still awake as well as how to control business processes, evaluate, and plan for long-term business processes in the future. The result is a Rating Scale obtained at DLTI is a Level Largely achieved and target Levels to be achieved is Fully achieved, so based on the analysis of gaps in the outline of the need for an increase in the Rating Scale of the existing conditions of the increase in activity with recommendations that maximizing the already good walking and doing activities to accelerate innovation in the achievement of business goals.